Effect of Moderate Hepatic Impairment on the Pharmacokinetics of Vadadustat, an Oral Hypoxia‐Inducible Factor Prolyl Hydroxylase Inhibitor. Issue 8 (4th March 2021) - Chavan, Ajit; Burke, Leontia; Sawant, Rishikesh; Navarro‐Gonzales, Pamela; Vargo, Dennis; Paulson, Susan K.
Abstract: Vadadustat is a hypoxia‐inducible factor prolyl hydroxylase inhibitor in development for the treatment of anemia of chronic kidney disease. This phase 1, open‐label, parallel‐group, single‐dose study evaluated the pharmacokinetics of 450‐mg vadadustat in adults with moderate hepatic impairment (Child‐Pugh class B) vs those with normal hepatic function. Primary end points were area under the plasma concentration–time curve (AUC) from dosing to last concentration and to infinity, as well as maximum concentration (Cmax ); additional pharmacokinetic parameters included time to Cmax (Tmax ) and half‐life. Safety and tolerability were also assessed. All enrolled participants (n = 16) completed the study. Demographics were similar in both groups (overall, 100% White; 62.5% female; mean age, 59.2 years). Vadadustat plasma exposure was higher in the moderate hepatic impairment group, whereas maximum concentration was similar between groups. Point estimates of the hepatic impairment : normal geometric mean ratios (90% confidence interval) for AUC from dosing to last concentration, AUC from dosing to infinity, and Cmax were 1.05 (0.82‐1.35), 1.06 (0.82‐1.36), and 1.02 (0.79‐1.32), respectively. Mean elimination half‐life was 5.8 and 7.8 hours in the normal and hepatic impairment groups, respectively. Treatment‐emergent adverse events were mostly mild in severity, and vadadustat was generally well tolerated. In conclusion, moderate hepatic impairment did not significantly impact vadadustat systemic exposure, and mild hepatic impairment is unlikely to alter vadadustat exposure.